An Analysis of Ecological Networks as an Instrument to Quantify Sustainability. An Application on the Virtual Water Metabolic Network of the Metropolitan District of Quito Ecuador. 2015 - Rosales, Francisco (2021)
Under the idea of ​​urban ecosystem, the objective of this study is to determine which internal patterns are those that determine whether or not the virtual water metabolic network (RMAV) of the Metropolitan District of Quito (DMQ) reaches a sustainable state at a moment in time. . For us, sustainability is a complete system feature, where the basic requirements are cross-border flows and entry and exit sinks. However, we emphasize what happens within the system, specifically the balance between efficiency and redundancy. To do this, we study the RMAV of the DMQ with the ecological network analysis (ENA) and we condense the evaluation into two classes of metrics, those that are focused on flow and those that are focused on information. The results show that it is a network where comprehensive relationships of exploitation dominate. The dominant ecological sectors of the ecological hierarchy are commerce (CM) and advanced manufacturing (MA), the most central node is commerce through which the largest amount of virtual water flows pass. RMAV is redundant to the detriment of efficiency, being located on the left side of the vitality window, out of sustainable positional balance.